Purification of anti-Mycobacterium tuberculosis MPT64 immunoglobulin-Y from egg-yolk supernatant using thiophilic adsorption chromatography - Kusuma, Sri Agung Fitri; Fadhlillah, Muhammad; Maisyarah, Intan Timur; Khairunnisa, Shintani Ayunda; Yusuf, Muhammad; Rukayadi, Yaya; Subroto, Toto (HH Publisher, 2024)
The significance of immunoglobulin Y (IgY) as a particular antibody equal to mammalian IgG is well understood. However, due to a lack of reliable purification procedures, producing highly pure IgY remains problematic. In this study, we aimed to optimize the recovery of pure IgY anti-MPT64 using thiophilic adsorption chromatography. The purification of IgY anti-MPT64 was achieved by initial PEG lipid precipitation, then an optimized purification by varying the gradient concentration of elution buffer into five steps gradient (0–20, 20–40, 40–60, 60–80, and 80–100%v/v) for three injection column volume (CV) each and two steps gradient (0–50 and 50–100%v/v) in eight CV for each concentration. The obtained IgY was characterized by SDS-PAGE and dot-blot then determined its content levels using the Lowry method. The results showed that the five steps gradient purification was found to provide a better purity level of IgY than the two steps gradient. However, the IgY content obtained in the two steps gradient purification (2.2632± 0.011 mg/mL) was higher than the five steps gradient purification (1.35482 ± 0.023 mg/mL). Nevertheless, both purified IgY results can recognize MPT64 protein through a dot blot test. Therefore, it can be summarized that thiophilic adsorption chromatography with five steps gradient of purification was an efficient process to obtain a higher purity of IgY anti-MPT64, especially to be targeted as a diagnostic kit component for MPT64 detection.